2017
DOI: 10.1039/c6nr08172j
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanotriangles: scale up and X-ray radiosensitization effects in mice

Abstract: In the past decade, there has been considerable interest in radiosensitization using gold nanoparticles that accumulate specifically in cancerous tissue while sparing normal tissues. Despite this interest, it remains unclear which nanoparticle morphologies, cellular uptake, or cytoplasmic distribution elicit optimal radiosensitization. We introduce gold nanotriangles (AuNTs) as a possible X-ray radiotherapy sensitizer. In this study, we first explored a large-scale synthetic method for the production of high q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
(44 reference statements)
1
45
0
Order By: Relevance
“…injection did not [ 47 ]. In a recent study, 24 h after the injection of 2.7 mg/kg PEGylated NPRs (61.51 ± 2.91 nm) (57 μg per mouse) it was found that the nanoparticles presented the highest level of accumulation in the spleen, whereas the liver and intestine had the next highest concentrations [ 49 ]. Moreover, these PEGylated NPRs did not provoke significant biochemical or hematological differences between untreated control mice and nanoparticles-treated mice, which is in accordance to our results.…”
Section: Discussionmentioning
confidence: 99%
“…injection did not [ 47 ]. In a recent study, 24 h after the injection of 2.7 mg/kg PEGylated NPRs (61.51 ± 2.91 nm) (57 μg per mouse) it was found that the nanoparticles presented the highest level of accumulation in the spleen, whereas the liver and intestine had the next highest concentrations [ 49 ]. Moreover, these PEGylated NPRs did not provoke significant biochemical or hematological differences between untreated control mice and nanoparticles-treated mice, which is in accordance to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Since GBM is considered as a radioresistant tumor [3] and most of the recurrence occurs in the radiotherapy field [4], radiosensitization of the tumor is an important target to improve the outcome in patients with GBM. Therefore, multiple radiosensitizing strategies are actively under development, including PI3K pathway inhibitors [5], DNA repair inhibitors [6], hyperthermia [7], aldehyde dehydrogenase inhibitors [8], and high atomic number (high-Z) metal nanoparticles (NPs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent attempts, GNPs are often coated with polyethylene glycol (“pegylated”) to decrease reticuloendothelial cell capture and conjugated to active cancer-specific targeting moieties to achieve favorable pharmacokinetics and durable localization to tumor cells 12 . Further experimentation using a variety of GNP shapes and sizes have shown differing rates of blood vessel extravasation and metabolic clearance 12 , 13 . Nanorods, for example, have been shown to offer superior intratumoral transport and distribution compared with nanospheres 14 .…”
Section: Introductionmentioning
confidence: 99%